Determinación de la susceptibilidad antimicrobiana con diferentes antibióticos contra Campylobacter spp aisladas en muestras cárnicas de bovinos - Peñaloza Vera, Dennise Michelle (2025)
This research aimed to determine the prevalence of Campylobacter spp. in bovine meat samples from Guaranda Canton, as well as to evaluate the antimicrobial activity and minimum inhibitory concentration (MIC) of Gentamicin, Penicillin G, and Sulfamethoxazole + Trimethoprim. The problem addressed relates to the presence of antibiotic-resistant pathogenic bacteria in food intended for human consumption, representing a public health risk. Sixty meat samples were analyzed using conventional microbiological methods (Gram staining, catalase, oxidase, and morphology), of which 54 samples (90%) tested positive for Campylobacter spp.. The presence of the pathogen was confirmed by culture on Skirrow medium under microaerophilic conditions. Subsequently, antimicrobial susceptibility was assessed using the disk diffusion method, testing three concentrations per antimicrobial (5, 10, and 15 µg). The results were classified as susceptible, intermediate, or resistant based on inhibition zone diameters. One-way ANOVA and Tukey's multiple comparison test were used to identify statistically significant differences among treatments (p < 0.05). The results showed that Gentamicin and Sulfamethoxazole + Trimethoprim were significantly more effective than Penicillin G, which exhibited high resistance levels across all concentrations. The relative MIC did not show a significant improvement with increased dosage. It is concluded that there is a high prevalence of Campylobacter spp. in bovine meat from Guaranda, and that Gentamicin and Sulfamethoxazole + Trimethoprim are effective therapeutic options against this pathogen, whereas Penicillin G proves inadequate. These findings underscore the importance of implementing microbiological surveillance strategies and promoting the rational use of antibiotics in the food industry.